Determinants Of Repeated Endowers Donation Intention In Cash Waqf:a Case Study In Majlis Agama Islam Dan Adat Melayu Perak (MAIPK) - Nur Diyana Azizi; Hisham Sabri; Syadiyah Abdul Shukor (Universitas Muhammadiyah Yogyakarta, 2024)
Non-Indexed Publication